Pengaruh Penggunaan Media Smart Wheel Terhadap Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun di SPS Shekinah Kids Kota Jambi - Theresia Natalia. S; Nyimas Muazzomi; Indryani (Yayasan Al-Afif, 2026)
Early reading skills are one of the most important aspects of a child's development. Some challenges include difficulty distinguishing between similar letters, not being able to use many words to express their desires or tell stories, and shyness in speaking in public due to a limited vocabulary. These early reading skills must be continuously honed and stimulated, which can be developed through the use of smart wheels. The purpose of this study was to determine the effect of using smart wheels on the early reading skills of children aged 5-6 years at Shekinah Kids Special School in Jambi City. This was an experimental study using a one-group pretest-posttest design. The population was 47 children. Purposive sampling was used, selecting 12 children from class B1. Data collection techniques included observation and documentation. The research instrument used was an observation sheet in accordance with the observation guide. Data analysis techniques included normality tests and homogeneity tests, and hypothesis testing using the t-test. The results of the study showed that Thitung > Ttabel, namely 16,096 > 2,200, so H0 was rejected and Ha was accepted, so it can be concluded that there is an Effect of Using Smart Wheel Media on the Beginning Reading Ability of Children Aged 5-6 Years at SPS Shekinah Kids, Jambi City